2021
DOI: 10.1111/jfpp.14946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium alginate coating containing clove ( Syzygium Aromaticum ) and lemon verbena ( Aloysia Citriodora ) essential oils and different packaging treatments on shelf life extension of refrigerated chicken breast

Abstract: The present study was conducted to preserve the microbial quality of chicken breast during storage time by using sodium alginate active coating solutions incorporated with different natural antimicrobials including Lemon Verbena (Le) and clove essential oils (Cl) which were added individually and in combination as well as packaging in Modified Atmosphere (M) (65% CO 2 , 30% N 2 , and 5% O 2) and in ambient atmosphere (A). The samples were stored in refrigeration condition for 15 days and were analyzed for tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 75 publications
7
16
0
Order By: Relevance
“…The results indicate the possibility of substituting conventional materials with sodium alginate/agar biopolymer. The same beneficial effect of natural extracts was shown by [ 177 ] when they packed chicken breast in polymer foils with the addition of essential oils of lemon and verbena or by Kang et al [ 178 ] when they packed low-fat frankfurters in sodium alginate film. Takma and Korel [ 179 ] produced active ethylene terephthalate (PET) films composed of chitosan and alginate as coatings incorporated with black cumin oil.…”
Section: Macroalgaesupporting
confidence: 61%
“…The results indicate the possibility of substituting conventional materials with sodium alginate/agar biopolymer. The same beneficial effect of natural extracts was shown by [ 177 ] when they packed chicken breast in polymer foils with the addition of essential oils of lemon and verbena or by Kang et al [ 178 ] when they packed low-fat frankfurters in sodium alginate film. Takma and Korel [ 179 ] produced active ethylene terephthalate (PET) films composed of chitosan and alginate as coatings incorporated with black cumin oil.…”
Section: Macroalgaesupporting
confidence: 61%
“…The authors acknowledge the beneficial effects of adding basil to the film matrix. The same beneficial effect of natural extracts was shown by Hosseini et al [ 52 ] when they packed chicken breast in polymer foils with the addition of essential oils of lemon and verbena or by Kang et al [ 53 ], when they packed low-fat frankfurters in sodium alginate film.…”
Section: Resultssupporting
confidence: 59%
“…Eugenol in clove and cinnamaldehyde in cinnamon can cause lysis to bacterial membranes and inhibit β-lactamase production in E. coli, as previously reported [11]. Previous studies also reported that clove and cinnamon essential oils can enhance the shelf life of chicken meat [12,13]. In this research, we test the antibacterial activity of clove and cinnamon essential oils against ESBLproducing bacteria.…”
Section: Introductionmentioning
confidence: 64%